EFEKTIFITAS PENGGUNAAN HUMOR DALAM KOMUNIKASI DOKTER TERHADAP PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH I LAGALIGO KABUPATEN LUWU TIMUR - Yanti, Icha Budha; Sugiana, Tantrika; Astraguna, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2025)
Effective communication between medical personnel and patients is an important component in the success of health services, but is still faced with various challenges, such as limited consultation time and rigid hierarchical relationships. This study aims to explore the role of humor in building therapeutic communication between doctors and inpatients at RSUD I Lagaligo, Luwu Timur Regency. The study used a qualitative-descriptive approach with data collection techniques through participatory observation, in-depth interviews with medical personnel and patients, and supporting documentation. Analysis was conducted using thematic method to identify communication patterns involving humor in clinical interaction. The results showed that humor, when used appropriately and contextually, is able to melt emotional tension, strengthen empathy, and increase patient openness in conveying honest and complete health information. In addition, the use of humor helped to create a more humane atmosphere in the medical relationship, which resulted in increased patient satisfaction and adherence to treatment. These findings confirm that humor is not just entertainment, but a potential communication strategy in strengthening the quality of healthcare. This study recommends empathic communication training that integrates the ethical use of humor for health workers